Hierarchically Porous, Laser-Pyrolyzed Carbon Electrode from Black Photoresist for On-Chip Microsupercapacitors - Soongeun Kwon; Hak-Jong Choi; Hyung Cheoul Shim; Yeoheung Yoon; Junhyoung Ahn; Hyungjun Lim; Geehong Kim; Kee-Bong Choi; JaeJong Lee (Nanomaterials, 2021)
We report a laser-pyrolyzed carbon (LPC) electrode prepared from a black photoresist for an on-chip microsupercapacitor (MSC). An interdigitated LPC electrode was fabricated by direct laser writing using a high-power carbon dioxide (CO2) laser to simultaneously carbonize and pattern a spin-coated black SU-8 film. Due to the high absorption of carbon blacks in black SU-8, the laser-irradiated SU-8 surface was directly exfoliated and carbonized by a fast photo-thermal reaction. Facile laser pyrolysis of black SU-8 provides a hierarchically macroporous, graphitic carbon structure with fewer defects (ID/IG = 0.19). The experimental conditions of CO2 direct laser writing were optimized to fabricate high-quality LPCs for MSC electrodes with low sheet resistance and good porosity. A typical MSC based on an LPC electrode showed a large areal capacitance of 1.26 mF cm−2 at a scan rate of 5 mV/s, outperforming most MSCs based on thermally pyrolyzed carbon. In addition, the results revealed that the high-resolution electrode pattern in the same footprint as that of the LPC-MSCs significantly affected the rate performance of the MSCs. Consequently, the proposed laser pyrolysis technique using black SU-8 provided simple and facile fabrication of porous, graphitic carbon electrodes for high-performance on-chip MSCs without high-temperature thermal pyrolysis.